Ballot papers and the practice of elections: Britain, France and the United States of America, c.1500–20001. Issue 241 (4th May 2015) - Crook, Malcolm; Crook, Tom
Abstract The humble ballot paper is a defining technology of elections throughout the world. This article interrogates its contested past by demonstrating – over a long period and in the context of three contrasting countries – how and why it emerged in the early modern period and how it was then used, abused and regulated in the context of the expanded, and eventually mass, electoral arenas of the nineteenth and twentieth centuries. Ironically, by the time that the ballot paper was firmly established, its monopoly was already being challenged by mechanical and then electronic media, which may eventually condemn it to extinction.